A high dispersibility paste suitable for MLCC roller printing and a preparation process thereof

By coating barium titanate particles with resin binders and combining pre-dispersion and homogenization steps, the problem of poor dispersion of barium titanate powder in the internal electrode paste of MLCCs was solved, achieving efficient roller printing and improved MLCC performance.

CN122677307BActive Publication Date: 2026-11-03CHANGDI NEW MATERIAL TECHNOLOGY (SHANGHAI) CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611161472.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-08-03
Publication Date
2026-11-03
Estimated Expiration
2046-08-03

AI Technical Summary

Technical Problem

In the roller printing process of MLCCs, barium titanate powder is difficult to achieve high dispersion in low viscosity systems, which leads to problems such as pores and discontinuities in the internal electrodes, and existing technologies are unable to solve this problem effectively.

Method used

Barium titanate particles are coated with resin binder to achieve high dispersibility through steric hindrance and repulsion. The coating layer is removed during the subsequent sintering process. Combined with pre-dispersion, stirring and homogenization steps, the blockage of the high-pressure homogenization chamber by agglomerated large particles is avoided.

Benefits of technology

It improves the efficiency and dispersibility of roller printing, avoids the impact of agglomerated large particles on dispersion performance, ensures the overall performance of MLCCs, and is suitable for roller printing of various specifications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122677307B_ABST
    Figure CN122677307B_ABST
Patent Text Reader

Abstract

The application relates to the technical field of multilayer ceramic capacitors, and particularly discloses a high-dispersibility slurry suitable for MLCC roller printing and a preparation process thereof, and the high-dispersibility slurry suitable for MLCC roller printing comprises the following raw materials in percentage by mass: 50-65% of nickel powder, 5-10% of resin-coated barium titanate, 1-4% of a dispersant, and 22-40% of a binder, wherein the particle size of the nickel powder is 150-400 nm, the particle size of the barium titanate in the resin-coated barium titanate is 20-200 nm, and the resin in the resin-coated barium titanate is made of one or more of methyl methacrylate, hydroxyethyl methacrylate, isobutyl acrylate and hydroxypropyl methacrylate. The high-dispersibility slurry suitable for MLCC roller printing prepared by the application improves the efficiency of roller printing by using coated barium titanate, and realizes high dispersibility of barium titanate particles in a low-viscosity system.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of multilayer ceramic capacitor technology, and in particular to a highly dispersible slurry suitable for MLCC roller printing and its preparation process. Background Technology

[0002] MLCC (Multi-layer Ceramic Capacitors) is an abbreviation for multilayer ceramic capacitors. It is an electronic component formed by laminating and co-firing multiple layers of ceramic dielectric and printed internal electrode paste, resulting in a monolithic appearance. MLCCs have a wide range of applications, including mobile electronic devices, process equipment, and medical devices.

[0003] Screen printing is a commonly used printing method in MLCC manufacturing, but its production efficiency is relatively low. Roller printing offers advantages such as high efficiency, high precision, and strong adaptability, but it requires low viscosity and high dispersibility in the internal electrode slurry. However, both the nickel powder and barium titanate powder inside the slurry are nanoparticles, and the particle size of barium titanate powder is much smaller than that of nickel powder. This makes it easy for barium titanate powder to agglomerate in the slurry system, making it difficult to achieve high dispersibility. Using a three-roll mill, sand mill, or homogenizer cannot effectively improve dispersibility; on the contrary, increasing the number of dispersion cycles can affect the powder morphology, thereby impacting the performance of the MLCC.

[0004] Therefore, in order to prevent back-end sintering problems such as voids and discontinuities in the internal electrodes of MLCCs, maintaining the high dispersibility of barium titanate particles in a low-viscosity system is a technical bottleneck that urgently needs to be overcome. Summary of the Invention

[0005] In order to maintain the high dispersibility of barium titanate particles in a low viscosity system, this application provides a highly dispersible slurry suitable for MLCC roller printing and its preparation process.

[0006] In a first aspect, this application provides a highly dispersible paste suitable for MLCC roller printing, employing the following technical solution: A highly dispersible paste suitable for MLCC roller printing comprises the following raw materials in weight percentages: Nickel powder 50-65% 5-10% barium titanate coated with resin Dispersant 1-4% Adhesive 22-40%, The nickel powder has a particle size of 150-400 nm, the barium titanate in the resin-coated barium titanate has a particle size of 20-200 nm, and the resin in the resin-coated barium titanate is made from one or more of methyl methacrylate, hydroxyethyl methacrylate, isobutyl acrylate, and hydroxypropyl methacrylate.

[0007] By employing the above technical solution, barium titanate particles that are difficult to disperse are coated with a resin binder material to obtain resin-coated barium titanate. On the one hand, this reduces and shields the agglomeration of the barium titanate particles themselves. The presence of the coating layer generates steric repulsion between the resin-coated barium titanate particles, achieving high dispersibility of the barium titanate particles. Moreover, the resin-coated barium titanate can better coat the surface of the nickel powder particles. On the other hand, in the subsequent MLCC preparation process, the resin coating on the surface of the barium titanate particles can be removed through the sintering step, avoiding any impact on the overall performance. In addition, the coated barium titanate is suitable for roller printing of various specifications, while directly coating barium titanate particles on the outside of nickel powder particles requires adjustment of the layer thickness and particle size of the barium titanate particles. This demonstrates that coated barium titanate improves the efficiency of roller printing and achieves high dispersibility in low-viscosity systems.

[0008] Optionally, the dispersant includes dispersant one and dispersant two, wherein the mass percentage of dispersant one is 0.5-2% and the mass percentage of dispersant two is 0.5-2%.

[0009] Optionally, the first dispersant is selected from one or more of NK2208, NK2210, NK2300 and NK250 from Interno International Industries Ltd., and the second dispersant is selected from one or more of NK2476, NK2480, NK2532 and NK2544 from Interno International Industries Ltd.

[0010] Optionally, the adhesive is composed of an adhesive resin and an adhesive solvent, wherein the mass ratio of the adhesive resin to the adhesive solvent is 2-7:93-98.

[0011] Optionally, the adhesive resin is selected from one or more of ethyl cellulose, acrylic resin, polyvinyl butyral, phenolic resin, amino resin, maleic anhydride resin, and epoxy resin, and the adhesive solvent is selected from one or more of terpineol, isoborneol acetate, diethylene glycol monomethyl ether, ethylene glycol monoethyl ether, and propylene glycol ether.

[0012] Secondly, this application provides a process for preparing a highly dispersible slurry suitable for MLCC roller printing, using the following technical solution: A process for preparing a highly dispersible paste suitable for MLCC roller printing includes the following steps: S1. The dispersant includes dispersant one and dispersant two. Nickel powder, dispersant one and binder are added to a planetary mixer. The speed is set to 40-60 r / min, the speed of the dispersing disc is 1000-1200 r / min, and the stirring time is 20-30 min. S2. Stop stirring, use a scraper to scrape the unstirred powder from the stirring rod and the wall into the slurry, and stir again at the same speed for 10-20 minutes to obtain nickel powder slurry; S3. Transfer the nickel powder slurry to a sand mill and mill it 20-40 times at a speed of 1500-2500 rpm. During this period, take a sample of the nickel powder slurry every 10 milling cycles and observe the dispersion effect under a light microscope until the dispersion effect meets the standard. Specifically, after sampling, a 200μm thick film layer of nickel powder slurry sample is scraped onto a glass slide using a wire rod. After drying, the sample is observed under an optical microscope to see if there are large particles or agglomeration. If so, the grinding continues; if not, it is considered to meet the standard. S4. Transfer the sand-ground nickel powder slurry to a planetary mixer, add resin-coated barium titanate and dispersant II, set the speed to 10-30 r / min, the dispersion disc speed to 100-500 r / min, and the mixing time to 5-10 min. S5. When no barium titanate powder is visible on the surface of the slurry, stop stirring and scrape the unstirred powder from the stirring rod and wall into the slurry with a scraper. Then set the rotation speed to 60-80 r / min, the dispersion disc speed to 1200-1400 r / min, and the stirring time to 30-40 min. S6. Transfer the mixed slurry to a high-pressure homogenizer, turn on the vacuum pump, set the air pressure to -0.8 to -1.0 MPa, set the homogenization pressure to 1500-2000 bar, and homogenize 2-5 times. S7. Transfer the homogenized slurry to a screw filter and filter it with a 3-5μm filter element to obtain a highly dispersible slurry suitable for MLCC roller printing.

[0013] By adopting the above technical solution, the nickel powder slurry is first pre-dispersed, then the barium titanate is coated with resin and stirred and dispersed, and finally homogenized and filtered. Compared with the existing technology of directly homogenizing nickel powder, barium titanate particles and binder together under high pressure, this method can effectively avoid the blockage of the high pressure homogenization chamber by agglomerated large particles, which would affect the dispersion performance.

[0014] Optionally, the first dispersant is selected from one or more of NK2208, NK2210, NK2300 and NK250 from Interno International Industries Ltd., and the second dispersant is selected from one or more of NK2476, NK2480, NK2532 and NK2544 from Interno International Industries Ltd.

[0015] By adopting the above technical solution, the two dispersion steps can effectively improve the dispersibility of resin-coated barium titanate in nickel powder slurry.

[0016] Optionally, the resin-coated barium titanate is prepared using the following steps: P1. Take barium titanate powder, ultrasonically disperse it in H2O2 solution, heat it under reflux, filter it, and dry it in a vacuum drying oven at 100℃ for 12 hours to obtain pretreated barium titanate particles. P2. Dissolve the silane coupling agent in an ethanol solution, add oxalic acid to adjust the pH to 1-3, and then use ultrasonic dispersion to hydrolyze the solution to obtain a silane coupling agent dispersion. P3. Add the pretreated barium titanate particles to the silane coupling agent dispersion and ultrasonically disperse until uniformly mixed to obtain a mixed dispersion. P4. Transfer the mixed dispersion to a three-necked flask equipped with a stirrer, reflux condenser and dropping funnel, add DMF solution and AIBN dropwise, and add resin monomer dropwise at a rate of 1 drop / 10s under water bath heating conditions, and stir the reaction. P5. The product obtained in P4 was filtered, washed with acetone solution, then washed with ethanol and water, dried under vacuum for 12 hours, and then ground to obtain resin-coated barium titanate.

[0017] By adopting the above technical solution, firstly, the strong oxidizing property of H2O2 is used to uniformly form hydroxyl groups on the surface of barium titanate particles under ultrasonic dispersion. Then, the silane coupling agent is hydrolyzed into silanol under acidic conditions, and dehydrated and condensed with the hydroxyl groups on the surface of barium titanate to form a Si-O-BaTiO3 structure with vinyl groups. The initiator decomposes under heating conditions to generate free radicals, which initiates a chain polymerization reaction between the unsaturated double bonds in the resin monomer and the vinyl groups in the Si-O-BaTiO3 structure, thereby forming a resin adhesive layer on the surface of barium titanate.

[0018] Optionally, in step P2, the silane coupling agent is selected from one or more of KH-570, A-151, A-171, and A-172.

[0019] In summary, this application includes at least one of the following beneficial technical effects: 1. Barium titanate particles that are difficult to disperse are coated with a resin binder to obtain resin-coated barium titanate. This process weakens and shields the agglomeration of barium titanate particles. The coating layer creates steric hindrance and repulsion between the resin-coated barium titanate particles, achieving high dispersibility. Furthermore, the resin-coated barium titanate can better coat the surface of nickel powder particles. On the other hand, during the subsequent MLCC manufacturing process, the resin coating on the surface of the barium titanate particles can be removed through a sintering step, avoiding any impact on the overall performance. In addition, coated barium titanate is suitable for roller printing of various sizes, whereas directly coating barium titanate particles onto nickel powder particles requires adjusting the layer thickness and particle size. Therefore, coated barium titanate improves the efficiency of roller printing and maintains high dispersibility in low-viscosity systems. 2. First, the nickel powder slurry is pre-dispersed, then the barium titanate is coated with resin and stirred and dispersed, and finally homogenized and filtered. Compared with the existing technology of directly homogenizing nickel powder, barium titanate particles and binder together under high pressure, this method can effectively avoid the blockage of the high pressure homogenization chamber by agglomerated large particles, which would affect the dispersion performance. 3. First, the strong oxidizing properties of H2O2 are used to uniformly form hydroxyl groups on the surface of barium titanate particles under ultrasonic dispersion. Then, the silane coupling agent is hydrolyzed into silanol under acidic conditions, and dehydrated and condensed with the hydroxyl groups on the surface of barium titanate to form a Si-O-BaTiO3 structure with vinyl groups. The initiator decomposes under heating conditions to generate free radicals, which initiates a chain polymerization reaction between the unsaturated double bonds in the resin monomer and the vinyl groups in the Si-O-BaTiO3 structure, thereby forming a resin binder layer on the surface of barium titanate. Attached Figure Description

[0020] Figure 1 This is an electron microscope image of the resin-coated barium titanate prepared in Example 1.

[0021] Figure 2 This is an electron microscope image of a highly dispersible paste suitable for MLCC roller printing in Example 1.

[0022] Figure 3 This is a photomicrograph of roller printing using a highly dispersible paste suitable for MLCC roller printing as described in Example 1.

[0023] Figure 4 This is a photomicrograph of roller printing using a highly dispersible slurry suitable for MLCC roller printing as described in Example 2.

[0024] Figure 5 This is a photomicrograph of roller printing using a highly dispersible slurry suitable for MLCC roller printing as described in Example 3.

[0025] Figure 6 This is an electron microscope image of one type of MLCC slurry in Comparative Example 1.

[0026] Figure 7 This is a photomicrograph of roller printing using one of the MLCC pastes in Comparative Example 1.

[0027] Figure 8 This is a glossy image of roller printing using one of the MLCC pastes in Comparative Example 2.

[0028] Figure 9 This is a glossy image of roller printing using one of the MLCC pastes in Comparative Example 3. Detailed Implementation

[0029] The following is in conjunction with the appendix Figure 1-9 This application will be described in further detail.

[0030] Performance testing

[0031] Experiment 1: Surface Roughness Test According to GB / T 1031-2009, the slurries prepared in the examples and comparative examples were coated on thin strips of the same specifications, and the surface roughness of the MLCC slurries prepared in the examples and comparative examples was tested.

[0032] Experiment 2: Viscosity Test According to GB / T 17473.5-2008, the viscosity of the MLCC slurry prepared in the examples and comparative examples was tested. The viscosity was measured at 25°C using a No. 14 rotor at a speed of 10 revolutions per minute.

[0033] Experiment 3: Temperature Coefficient of Capacitor Detection According to JJG183-2017, the slurries prepared in the examples and comparative examples were coated onto thin strips of the same specifications to form MLCCs, and the capacitance value and capacitance temperature coefficient were tested.

[0034] Experiment 4: Failure Rate Test According to GB / T 1772-1979, the slurries prepared in the examples and comparative examples were coated onto thin strips of the same specifications to form MLCCs. Under the condition of 125°C, three times the rated voltage (3Ur) was applied for 125 hours to test the failure rate of the MLCC slurries prepared in the examples and comparative examples.

[0035] Preparation Example Preparation Example 1 A resin-coated barium titanate is prepared by the following steps: A1. Take 100g of barium titanate powder and ultrasonically disperse it in 800mL of 30% H2O2 solution. Heat the oil bath to 100℃ and reflux for 4h. After filtration, put it in a vacuum drying oven at 100℃ and dry for 12h to obtain pretreated barium titanate particles. A2. Dissolve 10g of silane coupling agent KH-570 in 600mL of 95% ethanol solution, add oxalic acid to adjust the pH to 3, and ultrasonically disperse for 2h to hydrolyze, to obtain silane coupling agent dispersion. A3. Add 15g of pretreated barium titanate particles to 150mL of silane coupling agent dispersion and ultrasonically disperse for 4h until uniformly mixed to obtain a mixed dispersion. A4. Transfer the mixed dispersion to a three-necked flask equipped with a stirrer, reflux condenser and dropping funnel, add 50 mL of 99.98% DMF solution and add 0.3 g of AIBN dropwise. Under the heating condition of 80℃ water bath, add 150 g of methyl methacrylate dropwise at a rate of 1 drop / 10 s and stir the reaction for 4 h. A5. Filter the product obtained from the reaction in step A4, wash it with acetone solution, then wash it with ethanol and water, dry it under vacuum for 12 hours, and then grind it to obtain resin-coated barium titanate.

[0036] Reference Figure 1 The barium titanate surface is uniformly coated with a layer of resin binder and exhibits good dispersion uniformity.

[0037] Preparation Example 2 A resin-coated barium titanate is prepared by the following steps: A1. Take 100g of barium titanate powder and ultrasonically disperse it in 800mL of 30% H2O2 solution. Heat the solution in an oil bath to 105℃ and reflux for 3h. After filtration, dry it in a vacuum drying oven at 100℃ for 12h to obtain pretreated barium titanate particles. A2. Dissolve 10g of silane coupling agent KH-570 in 600mL of 95% ethanol solution, add oxalic acid to adjust the pH to 2, and sonicate for 1.5h to hydrolyze and obtain silane coupling agent dispersion. A3. Add 15g of pretreated barium titanate particles to 150mL of silane coupling agent dispersion and ultrasonically disperse for 3h until uniformly mixed to obtain a mixed dispersion. A4. Transfer the mixed dispersion to a three-necked flask equipped with a stirrer, reflux condenser and dropping funnel, add 50 mL of 99.98% DMF solution and add 0.3 g of AIBN dropwise. Under the condition of heating in an 80°C water bath, add 150 g of hydroxyethyl methacrylate dropwise at a rate of 1 drop / 10 s and stir the reaction for 3 h. A5. Filter the product obtained in step A4, wash it with acetone solution, then wash it with ethanol and water, vacuum dry it for 15 hours, and then grind it to obtain resin-coated barium titanate.

[0038] Preparation Example 3 A resin-coated barium titanate is prepared by the following steps: A1. Take 100g of barium titanate powder and ultrasonically disperse it in 800mL of 30% H2O2 solution. Heat the solution in an oil bath to 110℃ and reflux for 2h. After filtration, dry it in a vacuum drying oven at 100℃ for 12h to obtain pretreated barium titanate particles. A2. Dissolve 10g of silane coupling agent KH-570 in 600mL of 95% ethanol solution, add oxalic acid to adjust the pH to 1, and sonicate for 1h to hydrolyze the solution to obtain a silane coupling agent dispersion. A3. Add 15g of pretreated barium titanate particles to 150mL of silane coupling agent dispersion and ultrasonically disperse for 2h until uniformly mixed to obtain a mixed dispersion. A4. Transfer the mixed dispersion to a three-necked flask equipped with a stirrer, reflux condenser and dropping funnel, add 50 mL of 99.98% DMF solution and add 0.3 g of AIBN dropwise. Under the condition of heating in an 80°C water bath, add 150 g of hydroxypropyl methacrylate dropwise at a rate of 1 drop / 10 s and stir the reaction for 2 h. A5. Filter the product obtained in step A4, wash it with acetone solution, then wash it with ethanol and water, vacuum dry it for 18 hours, and then grind it to obtain resin-coated barium titanate.

[0039] Example

[0040] Example 1

[0041] A highly dispersible paste suitable for MLCC roller printing is prepared by the following steps: B1. Add nickel powder, dispersant 1 and binder to the planetary mixer, set the speed to 60 r / min, the speed of the dispersing disc to 1000 r / min, and the mixing time to 20 min; B2. Stop stirring, use a scraper to scrape the unstirred powder from the stirring rod and the wall into the slurry, and stir again at the same speed for 20 minutes to obtain nickel powder slurry; B3. Transfer the nickel powder slurry to a sand mill and mill it 40 times at a speed of 1500 rpm. During this process, take a sample of the nickel powder slurry every 10 milling cycles and observe the dispersion effect under a light microscope until the dispersion effect meets the standard. B4. Transfer the sand-milled nickel powder slurry to a planetary mixer, add the resin-coated barium titanate and dispersant II prepared in Preparation Example 1, set the speed to 20 r / min, the speed of the dispersion disk to 100 r / min, and the stirring time to 5 min. B5. When no barium titanate powder is visible on the surface of the slurry, stop stirring and scrape the unstirred powder from the stirring rod and wall into the slurry with a scraper. Then set the rotation speed to 60 r / min, the dispersion disc speed to 1200 r / min, and the stirring time to 30 min. B6. Turn on the vacuum pump and set the air pressure to -0.8MPa. Transfer the mixed slurry to the high-pressure homogenizer, set the homogenization pressure to 1500 bar, and homogenize twice. B7. Transfer the homogenized slurry to a screw filter and filter it with a 3μm filter element to obtain a highly dispersible slurry suitable for MLCC roller printing.

[0042] The composition consists of 60% nickel powder, 7% resin-coated barium titanate, 1.5% dispersant one, 1.5% dispersant two, and 30% binder. The nickel powder has a particle size of 400 nm; the resin-coated barium titanate has a particle size of 100 nm. Dispersant 1 comprises the following components: NK2208:NK2300 = 1:1; Dispersant II comprises the following components: NK2476:NK2532 = 1:1; The binder comprises the following components: terpineol: ethyl cellulose: acrylic resin: polyvinyl butyral = 95: 2: 2: 1; The adhesive was prepared at a temperature of 80℃ for 24 hours.

[0043] Reference Figure 2 The slurry surface has good smoothness, and the barium titanate and resin binder uniformly and well coat the nickel powder particles to form a dense coating.

[0044] Reference Figure 3 The printed image is of high quality, with no obvious protrusions or depressions at the edges, indicating that the viscosity is within a suitable range and the dispersibility is good.

[0045] Example 2

[0046] A highly dispersible paste suitable for MLCC roller printing is prepared by the following steps: B1. Add nickel powder, dispersant 1 and binder to the planetary mixer, set the speed to 50 r / min, the speed of the dispersing disc to 1100 r / min, and the mixing time to 25 min; B2. Stop stirring, use a scraper to scrape the unstirred powder from the stirring rod and the wall into the slurry, and stir again at the same speed for 15 minutes to obtain nickel powder slurry; B3. Transfer the nickel powder slurry to a sand mill and mill it 30 times at 2000 rpm. Take a sample of the nickel powder slurry every 10 milling cycles and observe the dispersion effect under a light microscope until the dispersion effect meets the standard. B4. Transfer the sand-milled nickel powder slurry to a planetary mixer, add the resin-coated barium titanate and dispersant II prepared in Preparation Example 2, set the speed to 30 r / min, the dispersion disk speed to 300 r / min, and the stirring time to 10 min. B5. When no barium titanate powder is visible on the surface of the slurry, stop stirring and scrape the unstirred powder from the stirring rod and wall into the slurry with a scraper. Then set the speed to 70 r / min, the dispersion disc speed to 1300 r / min, and the stirring time to 35 min. B6. Turn on the vacuum pump and set the air pressure to -0.9MPa. Transfer the mixed slurry to the high-pressure homogenizer, set the homogenization pressure to 1800 bar, and homogenize 4 times. B7. Transfer the homogenized slurry to a screw filter and filter it with a 5μm filter element to obtain a highly dispersible slurry suitable for MLCC roller printing.

[0047] The composition consists of 55% nickel powder, 5% resin-coated barium titanate, 2% dispersant one, 2% dispersant two, and 36% binder. The nickel powder has a particle size of 300 nm; the resin-coated barium titanate has a particle size of 80 nm. Dispersant 1 comprises the following components: NK2210:NK250 = 1:2; Dispersant II comprises the following components: NK2480:NK2544 = 1:2; The binder comprises the following components: isoborneol acetate: ethyl cellulose: epoxy resin: polyvinyl butyral = 98:1:0.5:0.5; The adhesive was prepared at a temperature of 90℃ and for 36 hours.

[0048] Reference Figure 4 The printed image is complete, with slightly raised edges and no depressions, indicating that the viscosity is too low, causing the paste to seep outwards from the edges. This may be due to the high proportion of binder in the system, resulting in a high solvent content.

[0049] Example 3

[0050] A highly dispersible paste suitable for MLCC roller printing is prepared by the following steps: B1. Add nickel powder, dispersant 1 and binder to the planetary mixer, set the speed to 40 r / min, the speed of the dispersing disc to 1200 r / min, and the mixing time to 30 min; B2. Stop stirring, use a scraper to scrape the unstirred powder from the stirring rod and the wall into the slurry, and stir for another 10 minutes at the same speed to obtain nickel powder slurry; B3. Transfer the nickel powder slurry to a sand mill and mill it 20 times at a speed of 2500 rpm. During this process, take a sample of the nickel powder slurry every 10 milling cycles and observe the dispersion effect under a light microscope until the dispersion effect meets the standard. B4. Transfer the milled nickel powder slurry to a planetary mixer, add the resin-coated barium titanate and dispersant II prepared in Preparation Example 3, set the speed to 10 r / min, the dispersion disk speed to 500 r / min, and the stirring time to 8 min. B5. When no barium titanate powder is visible on the surface of the slurry, stop stirring and scrape the unstirred powder from the stirring rod and wall into the slurry with a scraper. Then set the rotation speed to 80 r / min, the dispersion disc speed to 1400 r / min, and the stirring time to 40 min. B6. Turn on the vacuum pump, set the air pressure to -1.0MPa, transfer the mixed slurry to the high-pressure homogenizer, set the homogenization pressure to 2000 bar, and homogenize 5 times. B7. Transfer the homogenized slurry to a screw filter and filter it with a 4μm filter element to obtain a highly dispersible slurry suitable for MLCC roller printing.

[0051] The composition consists of 65% nickel powder, 10% resin-coated barium titanate, 1% dispersant one, 1% dispersant two, and 23% binder. The nickel powder has a particle size of 200 nm; the resin-coated barium titanate has a particle size of 50 nm. Dispersant 1 comprises the following components: NK2210:NK2300 = 2:1; Dispersant II comprises the following components: NK2480:NK2532 = 2:1; The binder comprises the following components: diethylene glycol monomethyl ether: ethyl cellulose: amino resin: polyvinyl butyral = 93:3:2:2; The adhesive was prepared at a temperature of 70℃ and for 48 hours.

[0052] Reference Figure 5 The printed image surface is incomplete, with slightly raised edges and no depressions. This is caused by the high viscosity of the system. It's possible that the ratio of binder to dispersant is too low, resulting in a higher overall viscosity.

[0053] Comparative Example Comparative Example 1 An MLCC slurry is prepared by the following steps: C1. Add nickel powder, dispersant 1 and binder to a planetary mixer, set the speed to 60 r / min, the speed of the dispersing disc to 1000 r / min, and the mixing time to 20 min; C2. Stop stirring, use a scraper to scrape the unstirred powder from the stirring rod and the wall into the slurry, and stir for another 20 minutes at the same speed to obtain nickel powder slurry; C3. Transfer the nickel powder slurry to a sand mill and mill it 40 times at a speed of 1500 rpm. During this process, take a sample of the nickel powder slurry every 10 milling cycles and observe the dispersion effect under a light microscope until the dispersion effect meets the standard. C4. Transfer the milled nickel powder slurry to a planetary mixer, add untreated barium titanate powder and dispersant II, set the speed to 20 r / min, the dispersion disc speed to 100 r / min, and the mixing time to 5 min. C5. When no barium titanate powder is visible on the surface of the slurry, stop stirring and use a scraper to scrape the unstirred powder from the stirring rod and the wall into the slurry. Then set the rotation speed to 60 r / min, the dispersion disc speed to 1200 r / min, and the stirring time to 30 min. C6. Turn on the vacuum pump, set the air pressure to -0.8MPa, transfer the mixed slurry to the high-pressure homogenizer, set the homogenization pressure to 1500 bar, and homogenize twice. C7. Transfer the homogenized slurry to a screw filter and filter it with a 3μm filter element to obtain an MLCC slurry.

[0054] The composition consists of 60% nickel powder, 7% barium titanate powder, 1.5% dispersant one, 1.5% dispersant two, and 30% binder. Nickel powder has a particle size of 400 nm; barium titanate powder has a particle size of 100 nm. Dispersant 1 comprises the following components: NK2208:NK2300 = 1:1; Dispersant II comprises the following components: NK2476:NK2532 = 1:1; The binder comprises the following components: terpineol: ethyl cellulose: acrylic resin: polyvinyl butyral = 95: 2: 2: 1; The adhesive was prepared at a temperature of 80℃ and for 24 hours.

[0055] Reference Figure 6 The slurry surface has good smoothness, but it is covered with dense pores of varying sizes. This is because the barium titanate particles are not evenly dispersed, resulting in poor shrinkage matching between the agglomerated large particles and small particles.

[0056] Reference Figure 7 The printed image surface is intact, but the edges are noticeably protruding, which is caused by the high viscosity of the system.

[0057] Comparative Example 2 An MLCC slurry is prepared by the following steps: C1. Add nickel powder, dispersant 1 and binder to a planetary mixer, set the speed to 50 r / min, the speed of the dispersing disc to 1100 r / min, and the mixing time to 25 min; C2. Stop stirring, use a scraper to scrape the unstirred powder from the stirring rod and the wall into the slurry, and stir for another 15 minutes at the same speed to obtain nickel powder slurry; C3. Transfer the nickel powder slurry to a sand mill and mill it 30 times at 2000 rpm. During this process, take a sample of the nickel powder slurry every 10 milling cycles and observe the dispersion effect under a light microscope until the dispersion effect meets the standard. C4. Transfer the sand-ground nickel powder slurry to a planetary mixer, add untreated barium titanate powder and dispersant II, set the speed to 30 r / min, the dispersion disc speed to 300 r / min, and the mixing time to 10 min. C5. When no barium titanate powder is visible on the surface of the slurry, stop stirring and scrape the unstirred powder from the stirring rod and wall into the slurry with a scraper. Then set the rotation speed to 70 r / min, the dispersion disc speed to 1300 r / min, and the stirring time to 35 min. C6. Turn on the vacuum pump and set the air pressure to -0.9MPa. Transfer the mixed slurry to the high-pressure homogenizer, set the homogenization pressure to 1800 bar, and homogenize 4 times. C7. Transfer the homogenized slurry to a screw filter and filter it with a 5μm filter element to obtain an MLCC slurry.

[0058] Of these components, nickel powder accounts for 55%, barium titanate powder accounts for 5%, dispersant one accounts for 2%, dispersant two accounts for 2%, and binder accounts for 36%. Nickel powder has a particle size of 300 nm; barium titanate powder has a particle size of 80 nm. Dispersant 1 comprises the following components: NK2210:NK250 = 1:2; Dispersant II comprises the following components: NK2480:NK2544 = 1:2; The binder comprises the following components: isoborneol acetate: ethyl cellulose: epoxy resin: polyvinyl butyral = 98:1:0.5:0.5; The adhesive was prepared at a temperature of 90℃ and for 36 hours.

[0059] Reference Figure 8 The printed image surface is intact, but the edges are uneven and jagged. This may be caused by a combination of a high dispersant ratio and the failure of barium titanate particles to be highly dispersed.

[0060] Comparative Example 3 An MLCC slurry is prepared by the following steps: C1. Add nickel powder, dispersant 1 and binder to a planetary mixer, set the speed to 40 r / min, the speed of the dispersing disc to 1200 r / min, and the mixing time to 30 min; C2. Stop stirring, use a scraper to scrape the unstirred powder from the stirring rod and the wall into the slurry, and stir for another 10 minutes at the same speed to obtain nickel powder slurry; C3. Transfer the nickel powder slurry to a sand mill and mill it 20 times at a speed of 2500 rpm. During this process, take a sample of the nickel powder slurry every 10 milling cycles and observe the dispersion effect under a light microscope until the dispersion effect meets the standard. C4. Transfer the sand-ground nickel powder slurry to a planetary mixer, add untreated barium titanate powder and dispersant II, set the speed to 10 r / min, the dispersion disc speed to 500 r / min, and the mixing time to 8 min; C5. When no barium titanate powder is visible on the surface of the slurry, stop stirring and scrape the unstirred powder from the stirring rod and wall into the slurry with a scraper. Then set the rotation speed to 80 r / min, the dispersion disc speed to 1400 r / min, and the stirring time to 40 min. C6. Turn on the vacuum pump, set the air pressure to -1.0MPa, transfer the mixed slurry to the high-pressure homogenizer, set the homogenization pressure to 2000 bar, and homogenize 5 times. C7. Transfer the homogenized slurry to a screw filter and filter it with a 4μm filter element to obtain an MLCC slurry.

[0061] Of these components, nickel powder accounts for 65%, barium titanate powder accounts for 10%, dispersant one accounts for 1%, dispersant two accounts for 1%, and binder accounts for 23%. Nickel powder has a particle size of 200 nm; barium titanate powder has a particle size of 50 nm. Dispersant 1 comprises the following components: NK2210:NK2300 = 2:1; Dispersant II comprises the following components: NK2480:NK2532 = 2:1; The binder comprises the following components: diethylene glycol monomethyl ether: ethyl cellulose: amino resin: polyvinyl butyral = 93:3:2:2; The adhesive was prepared at a temperature of 70℃ and for 48 hours.

[0062] Reference Figure 9 The surface of the slurry is uneven and covered with dense, visible pores. This is caused by a low proportion of dispersant and the failure of barium titanate particles to disperse evenly.

[0063] The performance test results of Examples 1-3 and Comparative Examples 1-3 are shown in Table 1 below.

[0064] Table 1 Performance test results of Examples 1-3 and Comparative Examples 1-3

[0065] As can be seen from Examples 1-3, Comparative Examples 1-3, and Table 1, the roughness R of Examples 1-3 is... a It decreases gradually, which is related to the particle size of the nickel powder and barium titanate in the slurry. The smaller the particle size, the lower the R value. a The smaller the value of R, the better. t The difference is not significant and the values ​​are very small, indicating that the system is well dispersed. In contrast, R in proportions 1-3... a With R t The values ​​are all very large, with R in comparative example 1 being particularly high. a The largest, because the particle size is the largest in the system. R0 for Comparative Example 2 and Comparative Example 3. aThe values ​​are close because Comparative Example 2 used a larger amount of dispersant. R t The numerical values ​​indicate that the barium titanate dispersion effect in Comparative Examples 1-3 is poor. The viscosity data shows that the amount of dispersant has a significant impact, and the degree of dispersion directly affects the viscosity value. The capacitance, TCC, and failure rate values ​​indicate that unevenly dispersed barium titanate slurries have a significant impact on electrical properties. The capacitance values ​​of Examples 1-3 are all higher than those of Comparative Examples 1-3, and the TCC values ​​of Examples 1-3 are all within the range of -15 to +15, while those of Comparative Examples 1-3 are all outside the critical range. The failure rate data also shows that unevenly dispersed barium titanate slurries have a significantly increased failure rate.

[0066] Therefore, coating difficult-to-disperse barium titanate particles with a resin binder to obtain resin-coated barium titanate not only weakens and shields the agglomeration of barium titanate particles, achieving high dispersibility, but also allows the resin-coated barium titanate to better coat the surface of nickel powder particles, maintaining high dispersibility in low-viscosity systems. Furthermore, coated barium titanate is suitable for roller printing of various specifications, improving the efficiency of roller printing.

[0067] The above are all preferred embodiments of this application, and are not intended to limit the scope of protection of this application. Therefore, all equivalent changes made in accordance with the structure, shape and principle of this application should be covered within the scope of protection of this application.

Claims

1. A highly dispersible paste suitable for MLCC roller printing, characterized in that, The raw materials include the following percentages by weight: Nickel powder 50-65% 5-10% barium titanate coated with resin Dispersant 1-4% Adhesive 22-40%, The nickel powder has a particle size of 150-400 nm, the barium titanate in the resin-coated barium titanate has a particle size of 20-200 nm, and the resin in the resin-coated barium titanate is made from one or more of methyl methacrylate, hydroxyethyl methacrylate, isobutyl acrylate, and hydroxypropyl methacrylate.

2. The highly dispersible slurry suitable for MLCC roller printing according to claim 1, characterized in that: The dispersant includes dispersant one and dispersant two, wherein the mass percentage of dispersant one is 0.5-2% and the mass percentage of dispersant two is 0.5-2%.

3. The highly dispersible slurry suitable for MLCC roller printing according to claim 2, characterized in that: The first dispersant is selected from one or more of NK2208, NK2210, NK2300 and NK250, and the second dispersant is selected from one or more of NK2476, NK2480, NK2532 and NK2544.

4. The highly dispersible slurry suitable for MLCC roller printing according to claim 1, characterized in that: The adhesive is composed of an adhesive resin and an adhesive solvent, wherein the mass ratio of the adhesive resin to the adhesive solvent is 2-7:93-98.

5. A highly dispersible slurry suitable for MLCC roller printing according to claim 4, characterized in that: The adhesive resin is selected from one or more of ethyl cellulose, acrylic resin, polyvinyl butyral, phenolic resin, amino resin, maleic anhydride resin, and epoxy resin, and the adhesive solvent is selected from one or more of terpineol, isoborneol acetate, diethylene glycol monomethyl ether, ethylene glycol monoethyl ether, and propylene glycol ether.

6. The preparation process of a highly dispersible slurry suitable for MLCC roller printing as described in any one of claims 1-5, characterized in that, Includes the following steps: S1. The dispersant includes dispersant one and dispersant two. Nickel powder, dispersant one and binder are added to a planetary mixer. The speed is set to 40-60 r / min, the speed of the dispersing disc is 1000-1200 r / min, and the stirring time is 20-30 min. S2. Stop stirring, use a scraper to scrape the unstirred powder from the stirring rod and the wall into the slurry, and stir again at the same speed for 10-20 minutes to obtain nickel powder slurry; S3. Transfer the nickel powder slurry to a sand mill and mill it 20-40 times at a speed of 1500-2500 rpm. During this period, take a sample of the nickel powder slurry every 10 milling cycles and observe the sample under a light microscope to see if there are large particles or agglomeration. If so, continue milling. If not, it is considered to meet the standard. S4. Transfer the sand-ground nickel powder slurry to a planetary mixer, add resin-coated barium titanate and dispersant II, set the speed to 10-30 r / min, the dispersion disc speed to 100-500 r / min, and the mixing time to 5-10 min. S5. When no barium titanate powder is visible on the surface of the slurry, stop stirring and scrape the unstirred powder from the stirring rod and wall into the slurry with a scraper. Then set the rotation speed to 60-80 r / min, the dispersion disc speed to 1200-1400 r / min, and the stirring time to 30-40 min. S6. Transfer the mixed slurry to a high-pressure homogenizer, turn on the vacuum pump, set the air pressure to -0.8 to -1.0 MPa, set the homogenization pressure to 1500-2000 bar, and homogenize 2-5 times. S7. Transfer the homogenized slurry to a screw filter and filter it with a 3-5μm filter element to obtain a highly dispersible slurry suitable for MLCC roller printing.

7. The preparation process of a highly dispersible slurry suitable for MLCC roller printing according to claim 6, characterized in that: The first dispersant is selected from one or more of NK2208, NK2210, NK2300 and NK250, and the second dispersant is selected from one or more of NK2476, NK2480, NK2532 and NK2544.

8. The preparation process of a highly dispersible slurry suitable for MLCC roller printing according to claim 6, characterized in that, The resin-coated barium titanate is prepared using the following steps: P1. Take barium titanate powder, ultrasonically disperse it in H2O2 solution, heat it under reflux, filter it, and dry it in a vacuum drying oven at 100℃ for 12 hours to obtain pretreated barium titanate particles. P2. Dissolve the silane coupling agent in an ethanol solution, add oxalic acid to adjust the pH to 1-3, and then use ultrasonic dispersion to hydrolyze the solution to obtain a silane coupling agent dispersion. P3. Add the pretreated barium titanate particles to the silane coupling agent dispersion and ultrasonically disperse until uniformly mixed to obtain a mixed dispersion. P4. Transfer the mixed dispersion to a three-necked flask equipped with a stirrer, reflux condenser and dropping funnel, add DMF solution and AIBN dropwise, and add resin monomer dropwise at a rate of 1 drop / 10s under water bath heating conditions, and stir the reaction. P5. The product obtained in P4 was filtered, washed with acetone solution, then washed with ethanol and water, dried under vacuum for 12 hours, and then ground to obtain resin-coated barium titanate.

9. The preparation process of a highly dispersible slurry suitable for MLCC roller printing according to claim 8, characterized in that: In step P2, the silane coupling agent is selected from one or more of KH-570, A-151, A-171, and A-172.

Citation Information

Patent Citations

  • Nano barium titanate coated alkyd resin type printing ink

    CN104356751A

  • Diaphragm for lithium ion battery and preparation method of diaphragm

    CN119481585A